Testing the limits of the ‘joint account’ model of genetic information: a legal thought experiment - Foster, Charles (Journal of medical ethics, 2015)
We examine the likely reception in the courtroom of the ‘joint account’ model of genetic confidentiality. We conclude that the model, as modified by Gilbar and others, is workable and reflects, better than more conventional legal approaches, both the biological and psychological realities and the obligations owed under Articles 8 and 10 of the European Convention on Human Rights (ECHR).